A Voltage-Tuned Terahertz Absorber Based on MoS2/Graphene Nanoribbon Structure - Omnia Samy; Mohamed Belmoubarik; Taiichi Otsuji; Amine El Moutaouakil (Nanomaterials, 2023)
Terahertz frequency has promising applications in communication, security scanning, medical imaging, and industry. THz absorbers are one of the required components for future THz applications. However, nowadays, obtaining a high absorption, simple structure, and ultrathin absorber is a challenge. In this work, we present a thin THz absorber that can be easily tuned through the whole THz range (0.1–10 THz) by applying a low gate voltage (<1 V). The structure is based on cheap and abundant materials (MoS2/graphene). Nanoribbons of MoS2/graphene heterostructure are laid over a SiO2 substrate with an applied vertical gate voltage. The computational model shows that we can achieve an absorptance of approximately 50% of the incident light. The absorptance frequency can be tuned through varying the structure and the substrate dimensions, where the nanoribbon width can be varied approximately from 90 nm to 300 nm, while still covering the whole THz range. The structure performance is not affected by high temperatures (500 K and above), so it is thermally stable. The proposed structure represents a low-voltage, easily tunable, low-cost, and small-size THz absorber that can be used in imaging and detection. It is an alternative to expensive THz metamaterial-based absorbers.